Pengaruh Musik Klasik Terhadap Daya Ingat Jangka Pendek (Studi Pada Mahasiswa Universitas Nasional Pasim) - Leonardo Dian Saiya; Sri Mulyeni (Journal of Educational Innovation and Public Health, 2024)
Humans have extraordinary brain power, however, a method is also needed to optimize brain performance. One of them is short-term memory. Listening to classical music will provide calm and stimulate and regulate the brain's condition for concentration. Classical music can also balance the activity of the right and left brain and regulate brain waves in good condition when studying. The type of research used was pre-experimental with a one group pretest posttest design, with the aim of seeing the influence of classical music on short-term memory in first year students at Pasim National University, Bandung city. The data collection technique used was simple random sampling with a sample size of 10 people, the average value of short-term memory in the pretest (16.3), posttest (21.4), and the average value of increase (5.1). . From the results of this research, it is stated that classical music has an effect on short-term memory in Pasim National University students, with evidence that there is an increase in results from pretest to posttest.